STUDIES ON BIOCHEMICAL CHANGES IN SOYBEAN INFECTED WITH COLLETOTRICHUM TRUNCATUM (SCHW.) - S. S. CHAVAN,; A. P. SURYVANSHI, (The Bioscan, 2016)
Present study was carried out to evaluate the changes occurring in biochemical’s (viz., total phenols, OD, reducing sugar, non reducing sugar, total sugar, chlorophyll a, b and total chlorophyll) in two genotypes JS-335 (susceptible) and MAUS-71 (resistant) after infection by pathogen Colletotrichum truncatum (Schw.) which causes tremendous losses in soybean crop. Results revealed that in diseased foliage of both the soybean cultivars, the chlorophyll content was reduced drastically over healthy cultivars, but at higher rate in susceptible JS-335 (55.8, 71.8 and 64.3 per cent) than resistant variety MAUS-71 (4.1, 31.8 and 12.9 per cent). Total sugar, reducing sugar and non reducing sugar contents were higher in healthy leaves of susceptible genotypes (7.0, 4.6 and 2.4 mg/g respectively) than resistant ones (5.3, 3.7 and 1.6 mg/g, respectively). Decrease in sugar content was at higher rates in susceptible varieties compared to resistant and moderately resistant varieties. Total phenol (0.9 mg/ g) and OD phenol (0.3 mg/g) were higher in amounts in healthy leaves of resistant genotypes than susceptible (Total phenols: 0.5 mg/g and OD phenols: 0.3 mg/g). So, it is clear that the infection of C. truncatum causes drastic alternations in amounts of biochemicals in soybean crop.